PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA FISIK TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA MAKO CAKE AND BAKERY DEPOK - Sada Yusuf; Nurdinni Tilova (Journal of Research and Publication Innovation, 2025)
The research in this thesis is motivated by the phenomenon of the increasing number of companies in the food sector, especially bread. Competition is currently getting stronger and tighter, so the company must have a strong strategy to face this competition. One of the strong strategies, for example, is the improvement of the physical work environment infrastructure that supports employee productivity and the application of the right leadership style. This will increase employee productivity and produce output that is in accordance with the company's target. This study aims to examine the effect of Transformational Leadership Style and Physical Work Environment on Employee Productivity at Mako Cake and Bakery Depok, both separately and simultaneously. The method used is Saturated Sample with a population of 44, where all members of the population are used as respondents. Data were collected through observation and questionnaires, and analyzed using validity, reliability, classical assumptions, regression, correlation coefficient, coefficient of determination, and hypothesis testing. The results show that Transformational Leadership Style has a significant influence on Employee Productivity (tcount> ttable) with a regression equation Y = 11.025 + 0.776X1, and a correlation value of 0.779 which shows a strong relationship. Physical Work Environment also has a significant effect on Employee Productivity (tcount> ttable) with a regression equation Y = 10.863 + 0.852X2 and a correlation of 0.843 which indicates a strong relationship. Simultaneously, these two variables affect Employee Performance (F count > Ftable) with a regression equation Y = 8.547 + 0.284X1 + 0.621X2 and a correlation value of 0.860, indicating a strong relationship, while the coefficient of determination of 86% indicates 14% is influenced by other factors. This means that if there is an increase in the transformational leadership style variable and the physical work environment, employee work productivity will also increase. The variable that has the most dominant influence on employee work productivity is the physical work environment variable by 84.3%.